Understanding Your Online Ratings: A Methodological Analysis Using Urogynecologists in the United States. Issue 2 (March 2019) - Huber, Sarah A.; Priestley, Jennifer; Kasabwala, Khushabu; Gadidov, Bogdan; Culligan, Patrick
Abstract : Objective: The influence of online physician ratings is growing, yet their interpretation remains difficult. Our aim was to analyze the online content of urogynecologists on 1 website to transform these ratings into practical tools for care improvement. Methods: This cross-sectional analysis studied the ratings and reviews of every board-certified urogynecologist listed onHealthgrades.com . The ratio of 5:1 ratings was compared between various physician characteristics and practice qualities. Four investigators classified narrative reviews into one or more of the following themes: about the (1) physician, (2) clinical outcomes, (3) and/or staff. The content of the narrative reviews was analyzed, and word clouds were created to understand the primary motivators behind ratings. Results: In February 2018, the Healthgrades pages for 689 urogynecologists were evaluated, and 523 physicians were included in the study. Higher 5:1 ratios were found among men versus women (4.0 vs 3.0; P < 0.01), and OB-GYN–trained versus urology-trained (4.0 vs 2.2; P < 0.01) physicians. A benchmarking rubric was developed to illustrate the 5:1 ratio distribution for all physicians stratified by number of ratings. A total of 3300 narrative reviews were assigned themes with strong inter- and intrarater reliability (Table 3). Physician qualities most influenced extreme scores (1 or 5 stars), whereas average reviews were more influenced by staff. Commonly discussed physician qualities included professionalism, time with patient, and counseling. Conclusions: Using the 5:1 rating ratio and simplified review themes as tools, physicians can understand what their ratings signify both as an indicator of their online reputation compared with their peers and as a means for improving the patient experience.